A systematic review of health sciences students’ online learning during the COVID-19 pandemic - Abdull Mutalib, Abdull Assyaqireen; Md. Akim, Abdah; Jaafar, Mohamad Hasif (BioMed Central, 2022)
Background: This study aims to analyse the effectiveness of distance learning during the COVID-19 pandemic among undergraduate health sciences students using systematic review. Online learning has been chosen as the best approach to continue offering education in this pandemic era. Method: The screening process was done using Scopus, ScienceDirect and PubMed based on the eligibility criteria. Out of 1486 studies, 1269 were screened. A total of 64 eligible studies obtained were included in the quantitative analysis. Results were categorized into i) student attitudes (perceptions/satisfactions/engagements), and ii) student learning outcomes, and compared to the Kirkpatrick model. Results: Although facing difficulties, 50% of the studies was moderately satisfied with distance learning, while 36% was highly satisfied and 17% dissatisfied. Most studies (26%) reported flexibility in online learning. Internet issues (19%) and low interaction between learners and instructors (19%) were the most prevalent problems mentioned. Online education engages students better than traditional learning. The learning outcome was assessed using two categories: i) academic performance and ii) skill development. Most studies (72%) stated that online learning improves academic performance, 14% reported a drop, and 14% stated no effect, while an increase in clinical skills and communication skills were reported. Kirkpatrick evaluation revealed 80% of the studies obtained was evaluated at level 1 (reaction), 8% at level 2 (learning), 12% at level 3 (behaviour) and none at level 4 (results). Conclusion: Overall, this systematic review found that the online learning performed better than expected during COVID-19, but the data gained is insufficient to say it is beneficial when compared to other types of teaching approaches.